Extracellular Matrix-Induced GM-CSF and Hypoxia Promote Immune Control of Mycobacterium tuberculosis in Human In Vitro Granulomas - Arbués, Ainhoa; Schmidiger, Sarah; Kammüller, Michael; Portevin, Damien (Frontiers in Immunology, 2021)
Several cellular models have been developed with the aim to reproduce and dissect human granulomatous responses, the hallmark of tuberculosis (TB) immunopathogenesis in vitro. In that context, we compared two- (2D) versus three-dimensional (3D) granuloma models resulting from infection of human peripheral blood mononuclear cells with M. tuberculosis (Mtb) in the absence or presence of a collagen-based extracellular matrix (ECM). Granuloma formation was found to be significantly enhanced in the 2D model. This feature was associated with an earlier chemokine production and lymphocyte activation, but also a significantly increased bacterial burden. Remarkably, the reduction in Mtb burden in the 3D model correlated with an increase in GM-CSF production. GM-CSF, which is known to promote macrophage survival, was found to be inherently induced by the ECM. We observed that only 3D in vitro granulomas led to the accumulation of lipid inclusions within Mtb. Our data suggest that a hypoxic environment within the ECM could be responsible for this dormant-like Mtb phenotype. Furthermore, exposure to a TNF-alpha antagonist reverted Mtb dormancy, thereby mimicking the reactivation of TB observed in rheumatic patients receiving this therapy. To conclude, we showed that only in vitro granulomas generated in the presence of an ECM could recapitulate some clinically relevant features of granulomatous responses in TB. As such, this model constitutes a highly valuable tool to study the interplay between immunity and Mtb stress responses as well as to evaluate novel treatment strategies.